It Takes Two: A Longitudinal Dyadic Study on Predictors of Fertility Outcomes. Issue 5 (5th February 2013) - Hutteman, Roos; Bleidorn, Wiebke; Penke, Lars; Denissen, Jaap J. A.
Abstract: Objective: Although previous studies have found personality traits to be associated with reproductive behavior, it remains unclear whether there are dyadic associations between partners' personality and couples' decisional process to have children. The aim of the present study was to investigate the associations between partners' personality, parenthood expectations and intentions, and the couple's fertility outcomes one year later. Method: We used dyadic longitudinal data from 2, 482 couples with a mean age of 32.7 years ( SD  = 5.9) participating in the Panel Analysis of Intimate Relationships and Family Dynamics (PAIRFAM). Results: Self‐esteem, shyness, and aggressiveness of both partners were related to one's own and one's partner's expectations about parenthood. These expectations were associated with one's own and one's partner's intentions to become a parent, which in turn predicted the couple's actual fertility outcomes. Personality traits of both partners were directly associated with the fertility outcome, with self‐esteem of both partners and male aggressiveness predicting the couple's decision to have their first child. The effect of self‐esteem on the decision to become a parent was mediated by the partner's intention. Conclusions: In sum, our findings stress the importance of psychological factors in fertility outcomes and emphasize the role of dyadic processes.